The COVID-19 Vaccination Hesitancy Among the People With Inflammatory Bowel Disease in China: A Questionnaire Study - Wu, Xia; Lin, Jue; Buch, Heena; Ding, Quchen; Zhang, Faming; Cui, Bota; Ji, Guozhong (Frontiers in Public Health, 2021)
Objective: To explore the attitudes and views of patients with inflammatory bowel disease (IBD) on COVID-19 vaccines. Methods: An online interview questionnaire concerning the acceptance or hesitancy towards vaccination for COVID-19 was designed and 543 patients with IBD in China were invited to complete the structured self-administered anonymous questionnaire. Results: Of all the participants, 50.7% were indecisive about the vaccination and only 16.0% opted for it. Vaccination hesitancy was significantly associated with females and those without medical or biomedical background. The acceptance of COVID-19 vaccination was higher in participants with no history of immune-modifying therapies, especially in those without immunosuppressants. Participants who considered vaccination critically important to self-health or others’ health were more likely to choose immediate or later vaccination. Safety and potential adverse reactions, personal hypoimmunity, efficacy and reliability of COVID-19 vaccines were the top three concerns of participants that were independent of their willingness for vaccination. Conclusions: This study discloses the presence of hesitancy for COVID-19 vaccination in patients with IBD. Further studies are warranted to evaluate the efficacy and safety of COVID-19 vaccines in IBD individuals, with specific focus on the impact of immune-modifying therapies. Health education and recommendation from authoritative sources may facilitate COVID-19 vaccination efforts. Key words: inflammatory bowel disease, SARS-CoV-2 vaccination, perspective, willingness, immunocompromised population.